EP295/#872 Post operative complications following ovarian cancer surgery: risk factors and its impact on cancer specific survival. (4th December 2022) - Thomas, Vinotha; Sebastian, Ajit; George, Rachel; Thomas, Dhanya; Thomas, Anitha; Peedicayil, Abraham
Abstract : Objectives: 1.To audit complications following ovarian cancer surgery (Clavien-Dindo classification) and their impact on oncologic outcome 2. To determine risk factors associated with postoperative complications. Methods: Electronic medical records of women who underwent surgery for epithelial ovarian cancer between January 2016 – December 2018 were audited. Design : Retrospective nested case control study. Cases: Patients with post-operative complications. Control: Those without complications. Setting: Department of gynaecologic oncology. Statistical analysis: SPSS v20 was used to analyse data. Chi square/Fischer test, ANOVA and multivariate regression were used to assess risk factors of complications. Results: Over 36 months, 370 women underwent surgery .Fifty percent (188/370) underwent primary cytoreduction and 74% had advanced disease (273/370). Optimal cytoreduction was achieved in 84% (273/370). The post-operative complication rate was 35% (129/370), over a median period of 5 days (0 to 53) : 24 % (89/370) and 10% (37/370) had grade 1–2 complications and grade 3–4 complications respectively . The 30 day mortality was 0.8 % (3/370). Advanced disease (p=0.027), high complexity of surgery (p=0.015), and intraoperative blood loss (p=0.001) were independently associated with increased rate of complications. The median time to recur was 17 months (12.6 to 21.3 months). Kaplan-Meir curve for survival showed a median recurrence free period of 20, 13 and 11 months respectively in the complication free, grade 1–2 and grade 3–4 complication group respectively, with a log rank value of 0.214. Conclusions: Ovarian cancer surgery is associated with an acceptable complication rate and patients should be selected with discretion .